Medieval Coins from the Bolgar Settlement based on the Works in 1970 (from the collections of the State Historical Museum) - Aleksei I. Bugarchev; Stefaniya V. Ushakova (Археология евразийских степей, 2023)
The article deals with numismatic materials received by the State Historical Musum from Bolgar. Coins were found during archaeological works led by N.D. Aksenova in 1970 in the XXXV excavation. The total number of attributed coins is 43 copies, including 1 Samanid dirham of the XX century, 7 silver and 34 copper Juchid coins, as well as one Nizhny Novgorod copeck. All of them are kept in the State Historical Museum. The coinage of the middle of the XIII century includes 8 copper dinars, in the first quarter of the XIV century, 2 anepigraphic dirhams were issued. 25 puls belong to the period of the second and third trimester, including 4 coins with countermarks of the second half of the XIV century. Three specimens were also found in the excavation, issued at the beginning of the XV century – 2 Bolgar akcha and 1 Nizhny Novgorod copeck. At the end of the paper is a map, indicating the location of the excavation and a photo table, depicting16 coins.